Analysis of qPCR reference genes stability determination methods and a practical approach for efficiency calculation on a turbot (Scphthalmus maximus) gonad dataset - Robledo, D. (Diego); Hernández-Urcera, J. (Jorge); Cal, R. (Rosa); Pardo, B. (Belén); Sánchez, L. (Laura); Martínez, P. (Paulino); Viñas, A. (Ana) (BMC Genomics, 2014)
Gene expression analysis by reverse transcription quantitative PCR (qPCR) is the most widely used method for analyzing the expression of a moderate number of genes and also for the validation of microarray results. Several issues are crucial for a successful qPCR study, particularly the selection of internal reference genes for normalization and efficiency determination. There is no agreement on which method is the best to detect the most stable genes neither on how to perform efficiency determination. In this study we offer a comprehensive evaluation of the characteristics of reference gene selection methods and how to decide which one is more reliable when they show discordant outcomes. Also, we analyze the current efficiency calculation controversy. Our dataset is composed by gonad samples of turbot at different development times reared at different temperatures. Turbot (Scophthalmus maximus) is a relevant marine aquaculture European species with increasing production in the incoming years. Since females largely outgrow males, identification of genes related to sex determination, gonad development and reproductive behavior, and analysis of their expression profiles are of primary importance for turbot industry